Kontribusi Sosial Media Dalam Memasarkan Produk Home Industry Bagi UMKM Di Pulau Timor - Selus Paru Kelin; Bonie Empy Giri; Meinahen Budi Bansoma; Vasio Sarmento Soares (Jurnal Media Infotama, 2025)
The development of technology in the new era of digital marketing has transformed the way of life for modern society, where business owners now utilize digital platforms to broaden their knowledge, strengthen brand image, and enhance interaction with the products they produce. Micro, Small, and Medium Enterprises (MSMEs) need to have an understanding and expertise in digital technology, as well as use social media as a marketing tool to expand their market reach. Additionally, a deep understanding of the target audience and the types of media used becomes crucial for digital marketers in determining product marketing strategies.In the current digital era, particularly in rural areas, especially on Timor Island, known for its cultural diversity and natural resources, MSMEs in home industries play an important role in the local economy. Despite having great potential, many MSMEs on Timor Island still face challenges in effectively marketing their products due to a lack of understanding and skills in digital technology, hindering them from utilizing social media as an essential marketing tool. This research aims to explore the contribution of social media in marketing home industry products by MSMEs on Timor Island, focusing on barriers, consumer engagement levels, and strategies that can be employed. The research method used is a mixed-methods approach, combining qualitative and quantitative methods, to obtain a comprehensive picture involving 100 respondents and interviews with 50 MSME entrepreneurs. The results of the study show that social media platforms such as Facebook, WhatsApp, and Instagram play an important role in increasing product visibility, consumer interaction, and sales, but many MSME entrepreneurs have not fully utilized the potential of social media. It is hoped that this research will provide insights for MSMEs, the government, and academics to support the development of MSMEs on Timor Island through more effective utilization of social media.